Methods in Buddhist studies: essays in honor of Richard Payne - Mitchell, Scott A. (Bloomsbury, 2019)
"Both a demonstration of and critical self-reflection on method, this book explores how methodologies shape our understanding of the diversity of Buddhist traditions in the past and the present. International contributors from the West and Asia explore case studies and reflect on methods in the study of Buddhism, united in their debt to Richard K. Payne, the influential Buddhist studies scholar. Methods in Buddhist Studies features new translations of Buddhist works as well as ethnographic studies on contemporary Buddhism in the United States and China. Topics discussed include Buddhist practices in relation to food, material culture, and imperial rituals; the development of modern Buddhist universities; the construction of the canon from the perspective of history, textual analysis, and ritual studies; and the ethical obligations of scholars toward the subject of Buddhism itself. Chapters are drawn from Payne's students and his colleagues, demonstrating the breadth of his intellectual interests. Payne's scholarship has left a remarkable impact on the field, making this volume essential reading for students and scholars of contemporary Buddhism and Buddhist studies."--Bloomsbury publishing